Die skoolkomiteestelsel in die Unie van S.A. : 'n Kritiese-vergelykende studie - Van der Merwe, G. J.(Gerrit Johannes),1921- (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEd) -- University of Stellenbosch, 1957.